2016
DOI: 10.1177/1527002516665794
|View full text |Cite
|
Sign up to set email alerts
|

Does the Home Advantage Depend on Crowd Support? Evidence From Same-Stadium Derbies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 25 publications
8
106
2
2
Order By: Relevance
“…Third, we found that the home advantage in soccer is more outspoken when the number of spectators is higher and when the home team is substantially stronger (in terms of UEFA coefficient) than the away team. These findings are consistent with Nevill et al (1996), Goumas (2013), Ponzo and Scoppa (2018), and . Finally, no significant association was found with variables capturing derby matches and variables portraying the home advantage at the national level.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Third, we found that the home advantage in soccer is more outspoken when the number of spectators is higher and when the home team is substantially stronger (in terms of UEFA coefficient) than the away team. These findings are consistent with Nevill et al (1996), Goumas (2013), Ponzo and Scoppa (2018), and . Finally, no significant association was found with variables capturing derby matches and variables portraying the home advantage at the national level.…”
Section: Resultssupporting
confidence: 89%
“…For more information on the regulations of the two competitions and the rules of a soccer match, we refer to the UEFA website (http://www.uefa.com) and to FIFA (2017). Following the approach used by Ponzo and Scoppa (2018), we considered each match twice in our data, one time from the perspective of the home team and one time from the perspective of the away team. This generated a total of 4,024 observations at the team-match level.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This home advantage is mainly attributed to the support of the home crowd in combination with possibly biased referee decisions, players' familiarity with their stadium and travel fatigue of the away team (see, for example, Clarke and Norman (1995), Pollard (2006), Pollard and Armatas (2017) and Ponzo and Scoppa (2017)). Whether or not an artificial pitch introduces an additional home advantage has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For the highest German league, Buraimo et al (2010) find that teams that play in stadiums with running tracks have a smaller referee bias which they attribute to a bigger distance between play and audience. Ponzo and Scoppa (2018) analyze same-stadium derbies across Europe, i.e. matches between teams that share the same stadium.…”
mentioning
confidence: 99%